2017
DOI: 10.1177/1933719116678689
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Androstenediol in the Regulation of the Proliferative Process of Human Endometrial Cells

Abstract: Proliferation in endometria of women with polycystic ovarian syndrome (PCOS) is increased, similar to the biosynthesis of androstenediol (estrogenic metabolite). As previously shown, in human endometrial cells, androstenediol increases CYCLIN D1 levels and KI67 and decreases P27 content. The objective of the present investigation was to determine the mechanisms by which androstenediol promotes endometrial cell-cycle progression. Estrogen receptor α (ERα) activation and changes in CYCLIN D1 and P27 levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Interestingly, TNFR2 is more related to proliferative and proinflammatory process than to apoptosis, 28 which is concordant to the fact that women with PCOS have a higher risk of developing endometrial hyperplasia and endometrial adenoma or carcinoma. 29,30 Consequently, the failures in insulin signaling observed in endometrium from obese women with PCOS may be the result of an increase in TNF-a activity, which may negatively affect insulin action through different mechanisms. One of these mechanisms is the increase in interleukin (IL)-6 expression via NFkB activation, 19,20,31 since this proinflammatory cytokine is closely related to insulin resistance and increased serum levels have been detected in obese women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, TNFR2 is more related to proliferative and proinflammatory process than to apoptosis, 28 which is concordant to the fact that women with PCOS have a higher risk of developing endometrial hyperplasia and endometrial adenoma or carcinoma. 29,30 Consequently, the failures in insulin signaling observed in endometrium from obese women with PCOS may be the result of an increase in TNF-a activity, which may negatively affect insulin action through different mechanisms. One of these mechanisms is the increase in interleukin (IL)-6 expression via NFkB activation, 19,20,31 since this proinflammatory cytokine is closely related to insulin resistance and increased serum levels have been detected in obese women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TNFR2 is more related to proliferative and proinflammatory process than to apoptosis, 28 which is concordant to the fact that women with PCOS have a higher risk of developing endometrial hyperplasia and endometrial adenoma or carcinoma. 29,30…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced ER-α activation was associated with rare or absent apoptosis and increased in cell proliferation in the endometrium in the mid luteal phase [30,[36][37][38]. On the other hand, it is possible that high circulating estrogens as in patients performing ovarian stimulation to determine the apoptosis of the endometrial glandular cells, as showed by an experimental study by Chen et al [39].…”
Section: Estrogen Receptors (Er) Expression and Functionmentioning
confidence: 99%
“…In the endometrium of PCOS women the androgen receptor (AR) mRNA and protein expression is increased [23] and coactivators of AR were found to be overexpressed as well [37]. Among these coactivators, Melanoma-associated antigen 11 (MAGEA11) was showed to bind to AR resulting in alteration of window of implantation [11].…”
Section: Androgen Receptormentioning
confidence: 99%
See 1 more Smart Citation